An extended stochastic VIKOR model with decision maker's attitude towards risk - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Information Sciences)

Automated Model Verification using an Equivalence Test on a Reference Mode - Akbulut, Akin; Abke, Stephan; Laroque, Christoph (Proceedings of the 2017 Winter Simulation Conference)

Using Sentiment Analysis on Local Up-to-the-Minute News: An Integrated Approach - Kersting, Joschka; Geierhos, Michaela (Proceedings of the 23rd International Conference on Information and Software Technologies, Communications in Computer and Information Science)

Automatisierte Modellverifikation mithilfe einer Äquivalenzprüfung an einem Referenzmodell - Akbulut, Akin; Laroque, Christoph; Dangelmaier, Wilhelm

From User Demand to Software Service: Using Machine Learning to Automate the Requirements Specification Process - van Rooijen, Lorijn; Baeumer, Frederik Simon; Platenius, Marie Christin; Geierhos,, Michaela; Hamann, Heiko; Engels, Gregor

Guesswork? Resolving Vagueness in User-Generated Software Requirements - Geierhos, Michaela; Baeumer , Frederik Simon (Partiality and Underspecification in Information, Languages, and Knowledge)

Studying Software Descriptions in SourceForge and App Stores for a better Understanding of real-life Requirements - Baeumer, Frederik Simon; Markus, Dollmann (Proceedings of the 2nd ACM SIGSOFT International Workshop on App Market Analytics)

Studying Software Descriptions in SourceForge and App Stores for a better Understanding of real-life Requirements - Baeumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2nd ACM SIGSOFT International Workshop on App Market Analytics)

Production theory 1 - Dangelmaier, Wilhelm
n the multi-volume work on "Theory of Production", the production models and processes born today from practice are to be derived for the first time on a mathematically justified basis and thus also given the production economy a scientific basis. A constructivist point of view is to be set aside for “we just organized our company that way and it has proven itself”, and so the many descriptive “factory management teachings” are to be replaced. Volume 1 contains the basics of logic, set theory and algebra. The production-relevant conceptions of systems theory are for the first time completely mapped to constructs of formal logic, propositional and predicate logic consistently presented using examples. The predicate logic strikes the bow to the NC program; all parameters of a machining production are derived explicitly. An application example of the set-theoretical concepts is the computer-aided design, the relational calculus is mapped, for example, to product structures, replacement parts and identical parts. The basics of algebra deal in detail with the algebraic systems with internal connections that are important for engineering. Rotating tool magazines are mentioned here as an example. Algebraic systems with external links deal in particular with the handling of matrices. The basics of classifying, ordering and measuring conclude this volume. The basics of algebra deal in detail with the algebraic systems with internal connections that are important for engineering. Rotating tool magazines are mentioned here as an example. Algebraic systems with external links deal in particular with the handling of matrices. The basics of classifying, ordering and measuring complete this volume. The basics of algebra deal in detail with the algebraic systems with internal connections that are important for engineering. Rotating tool magazines are mentioned here as an example. Algebraic systems with external links deal in particular with the handling of matrices. The basics of classifying, ordering and measuring conclude this volume.

Production theory 2 - Dangelmaier, Wilhelm
In the multi-volume work on "Theory of Production", the production models and processes born today from practice are to be derived for the first time on a mathematically justified basis and thus also given the production economy a scientific basis. A constructivist point of view is to be set aside for “we just organized our company that way and it has proven itself”, and so the many descriptive “factory management teachings” are to be replaced. Volume 2 deals with the structures of production. Based on the newly interpreted construct of the “production point”, larger units are composed step by step: single-stage and multi-stage technical quantities. In addition, the production point integrates the subdivision used today in business administration into the object-oriented, activity favoring black box thinking and the functionalist view of consumption and production functions. The conceptual foundations are mainly algebraic input-output systems. Based on the structuring and parameterization options at the production point, alternative organizational concepts for single and multi-level productions are developed. For the engineering sciences, a detailed treatise on the evaluation of production success is particularly important in this volume, which systematically leads to product calculation and the planning of an economically successful production program. Based on the structuring and parameterization options at the production point, alternative organizational concepts for single and multi-level productions are developed. Particularly important for the engineering sciences is a detailed treatise in this volume on the evaluation of production success, which systematically leads to product calculation and the planning of an economically successful production program. Based on the structuring and parameterization options at the production point, alternative organizational concepts for single and multi-level productions are developed. For the engineering sciences, a detailed treatise on the evaluation of production success is particularly important in this volume, which systematically leads to product calculation and the planning of an economically successful production program.

Production theory 3 - Dangelmaier, Wilhelm
In the multi-volume work on "Theory of Production", the production models and processes born today from practice are to be derived for the first time on a mathematically justified basis and thus also given the production economy a scientific basis. A constructivist point of view is to be set aside for “we just organized our company that way and it has proven itself”, and so the many descriptive “factory management teachings” are to be replaced. Volume 3 deals with production processes in time. Ordinal and cardinal amounts of time lead to the system-theoretical definition of a process at the point of production and the possible understandings of processes and states. A main point here is the derivation of the common thinking in series production in terms of performance figures. Starting from the basic form of a time-based production, efficient dynamic events and processes are prepared. This creates the basis for the representation of the state of a general time system and the use of sequential machines. Time-invariant time systems and stochastic productions are the basis of robust production. The point of production and the time system find an ideal symbiosis in the use of finite automatons: A finite number of states together with a limited amount of inputs leads to state-driven production - one of the essential prerequisites for the realization of Industry 4.0. This creates the basis for the representation of the state of a general time system and the use of sequential machines. Time-invariant time systems and stochastic productions are the basis of robust production. The point of production and the time system find an ideal symbiosis in the use of finite automatons: A finite number of states together with a limited amount of inputs leads to state-driven production - one of the essential prerequisites for the realization of Industry 4.0. This creates the basis for the representation of the state of a general time system and the use of sequential machines. Time-invariant time systems and stochastic productions are the basis of robust production. The point of production and the time system find an ideal symbiosis in the use of finite automata: A finite number of states together with a limited number of inputs leads to state-driven production - one of the essential prerequisites for the realization of Industry 4.0.

Effektives Customer Relationship Management - Helmke, Stefan; Uebel, Matthias; Dangelmaier, Wilhelm

Developing and Using an Audience Response System - Kundisch, Dennis

Recombinant Service System Engineering - Beverungen, Daniel; Lüttenberg, Hedda; Wolf, Verena (Proceedings der 13. Internationalen Tagung Wirtschaftsinformatik (WI 2017))
Although many methods have been proposed for engineering services and customer solutions, most of these approaches give little consideration to recombinant service innovation. In an age of smart products and smart data, we can, however, expect that many of future service innovations need to be based on adding, transferring, dissociating, and associating existing value propositions. The purpose of this paper is to outline what properties constitute recombinant service innovation and to identify if current service engineering approaches fulfill these properties. Based on a conceptual in-depth analysis of 24 service engineering methods, we identify that most methods focus on designing value propositions instead of service systems, view service independent of physical goods, are linear or iterative, and incompletely address the mechanisms of recombinant innovation. We discuss how these deficiencies can be remedied and propose a first conceptual model of a revised se rvice system engineering approach.
Keywords: Service engineering; recombinant innovation; (product - )service system; literature analysis; new service development

Wer hat hier das Sagen? - Krebs, Benjamin; Wehner, Marius; Kabst, Rüdiger (Personalmagazin)

Nordeuropa hat´s nicht nötig - Krebs, Benjamin; Wehner, Marius; Kabst, Rüdiger (Personalmagazin)

Cranet Survey 2015/2016 - Stand der HR-Digitalisierung. - Rauterberg, Hannah; Krebs, Benjamin (Personalführung)

Decomposing the Variance of Consumer Ratings and the Impact on Price and Demand - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Information Systems Research)

Does the Framing of Progress Towards Virtual Rewards Matter? Empirical Evidence from an Online Community - Kundisch, Dennis; von Rechenberg, Tobias (Business & Information Systems Engineering)

Is it Worth the Effort? - A Decision Model to Evaluate Resource Interactions in IS Project Portfolios - Meier, Christian; Kundisch, Dennis; Willeke, Jochen (Business & Information Systems Engineering)

Strategische Erfolgsplanung für Produktinnovationen - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Lagerkapazitätsdimensionierung als betriebswirtschaftliches Entscheidungsproblem - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Webbasierte Classroom Response Systeme in der Hochschullehre - Eine designbasierte Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Zoyke, A.; Beutner, Marc; Herrmann, Philipp; Kundisch, Dennis; Magenheim, Johannes; Neugebauer, J. (Das Hochschulwesen)

When in Doubt Follow the Crowd: How Idea Quality Moderates the Effect of an Anchor on Idea Evaluation - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 38th International Conference on Information Systems (ICIS))

"What is it Good for - Absolutely Nothing?" Exploring the Influence of Task Meaning on Creativity in Crowdsourcing - Görzen, Thomas (Proceedings of the 38th International Conference on Information Systems (ICIS))

Aktuelle Fragestellungen zu Produktion, Logistik und Controlling

Bitte stimmen Sie jetzt ab! - Ein Erfahrungsbericht über das Audience Response System PINGO - Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius (Proceedings der 15. e-Learning Fachtagung Informatik (DELFI 2017))

Study? Now! - Evaluation einer gamifizierten App zur Überwindung von akademischer Prokrastination - Klingsieck, K.; Bomm, A.; Djawadi, Behnud; Fahr, Rene; Feldotto, M.; John, Thomas; Kundisch, Dennis; Skopalik, A. (Tagung der Fachgruppen Entwicklungspsychologie und Pädagogische Psychologie (PAEPSY))

Towards a Lean Approach to Gamifying Education - John, Thomas; Feldotto, M.; Hemsen, P.; Klingsieck, K.; Langendorf, Mike (Proceedings of the 24th European Conference on Information Systems (ECIS))

Achieving More by Paying Less? How Retailers can Benefit by Bidding Less Aggressively in Paid Search Auctions - Schlangenotto, Darius; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Making Gamification Easy for the Professor: Decoupling Game and Content with the StudyNow Mobile App - Feldotto, M.; John, Thomas; Kundisch, Dennis; Hemsen, P.; Klingsieck, K.; Skopalik, A. (Proceedings of the 12th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Decomposing the Variance of Online Consumer Ratings and the Impact on Price and Demand - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Workshop Theory in Economics of Information Systems (TEIS))

Using Information Cues to Identify High Quality Ideas in Crowd Evaluation - Görzen, Thomas; Kundisch, Dennis (2nd Workshop on IS Design and Economic Behavior (ISDEB))

Recommendation and Configuration of Value-Added Services for Repurposing Electric Vehicle Batteries: A Vertical Software Prototype - Klör, Benjamin; Monhof, Markus; Bräuer, Sebastian; Beverungen, Daniel (Proceedings of the 19th IEEE Conference on Business Informatics (CBI 2017))

The impact of customer reviews and advertisement efforts on the performance of experience goods in electronic markets - Frick, Bernd; Kaimann, Daniel (Applied Economics Letters)

Interaktive, digitale Einkaufserlebnisse in Innenstädten - Hendrik Betzing, Jan; Beverungen, Daniel; Becker, Jörg; Matzner, Martin; Schmitz, Gertrud; Bartelheimer, Christian; Berendes, Carsten Ingo; Braun, Marina; Gadeib, Andera; Hoffen}, Moritz {von; Schallenberg, Christian (HMD Praxis der Wirtschaftsinformatik)

Ensembles of Context and Form for Repurposing Electric Vehicle Batteries: An Exploratory Study - Beverungen, Daniel; Bräuer, Sebastian; Plenter, Florian; Klör, Benjamin; Monhof, Markus (Computer Science --- Research and Development)

Information systems for smart services - Beverungen, Daniel; Matzner, Martin; Janiesch, Christian (Information Systems and E-Business Management)
Digital interactions among businesses and consumers through powerful information systems and omnipresent connected devices establish today’s networked society. In this light, Service Science continues to take root as a research discipline that focuses on the integration of (digital) resources by service providers and service customers for value co-creation in service systems. Rapid advances in information technology allow for designing novel information systems that enable entirely new configurations of service systems. In turn, Service Science also leaves its mark on the design, adoption, and use of information systems and technology. With this special issue, we compile a set of timely papers that investigate selected facets of the complex interplay between information technology, information systems, and Service Science to design innovative IT artifacts for smart service. This editorial opens this special issue by elaborating on our understanding of smart service.<br
Keywords: Information system; Smart service; Service system

How to Handle Dilemmas in Triadic Service Relationships – An Exploratory Study. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 2017 Frontiers in Service Conference)

Tax loss carryforward disclosure and uncertainty - Flagmeier, Vanessa; Müller, Jens
We examine whether companies voluntarily disclose additional information about tax loss carryforwards when the recoverability is more uncertain. With this study, we aim to explain part of the huge cross-sectional variation in the tax footnote. To assess disclosure behavior, we hand-collect data from notes of large German firms’ IFRS financial statements and identify voluntarily disclosed information. First, our results support prior literature’s evidence of a considerable cross-sectional variation of disclosure in the tax footnote. Second, we find that uncertainty about the usability of tax losses has a significantly positive relation to the amount and quality of disclosure, controlling for other disclosure determinants derived from prior literature and for sample selection. Third, our results indicate that the observed disclosure behavior is not simply a reflection of the firm’s general disclosure behavior but specific to the tax footnote. These findings are robust to several historic and forward-looking indicators representing uncertainty. Our findings suggest that managers anticipate the investors’ need for more private information and disclose them voluntarily to reduce information asymmetries. This result indicates that part of the cross-sectional variation in the tax footnote can be explained by firms anticipating investors’ demand for additional information.

The information content of tax loss carryforwards: IAS 12 vs. valuation allowance - Flagmeier, Vanessa
This is the first study that analyzes the predictive ability of deferred tax information under IFRS. I examine whether deferred taxes provide information about future tax payments and future performance, using a German sample of IFRS firms. The focus on tax loss carryforwards enables a separation of the two relations, testing on the one hand, the relation between recognized deferred tax assets and future tax payments and on the other hand, the relation between the non-usable part of tax losses and future earnings. I find significantly negative coefficients for both deferred tax items, indicating that higher recognized deferred tax assets are associated with lower future tax payments and higher non-usable tax loss carryforwards with lower future performance. Additionally, I compare the tax accounts' predictive ability for a matched German and US sample and find no significant differences between firms reporting under IFRS and US-GAAP. Taken together, the evidence suggests that deferred tax items for tax loss carryforwards reported under IFRS provide useful information about future outcomes and that this predictive ability does not differ significantly from firms reporting under US-GAAP.

Unbekannte Praxis - Über die Schwierigkeit einiger Forscher, die Welt zu verstehen - Sloane, Peter F. E. (Zeitschrift für Berufs-und Wirtschaftspädagogik)

Slow Booms and Deep Busts: 160 Years of Business Cycles in Spain - Gries, Thomas; Fritz, Marlon; Feng, Yuanhua (Review of Economics)

Over-Paid Search: When Bricks-and-Mortar Retailers Should Not Use Paid Search - Schlangenotto, Darius; Kundisch, Dennis (Wirtschaftsinformatik Proceedings, Extended Abstract)

Certiﬁcation Matters for Service Markets - Jakobs, Marie-Christine; Krämer, Julia; van Straaten, Dirk; Lettmann, Theodor (The Ninth International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
Whenever customers have to decide between different instances of the same product, they are interested in buying the best product. In contrast, companies are interested in reducing the construction effort (and usually as a consequence thereof, the quality) to gain profit. The described setting is widely known as opposed preferences in quality of the product and also applies to the context of service-oriented computing. In general, service-oriented computing emphasizes the construction of large software systems out of existing services, where services are small and self-contained pieces of software that adhere to a specified interface. Several implementations of the same interface are considered as several instances of the same service. Thereby, customers are interested in buying the best service implementation for their service composition wrt. to metrics, such as costs, energy, memory consumption, or execution time. One way to ensure the service quality is to employ certificates, which can come in different kinds: Technical certificates proving correctness can be automatically constructed by the service provider and again be automatically checked by the user. Digital certificates allow proof of the integrity of a product. Other certificates might be rolled out if service providers follow a good software construction principle, which is checked in annual audits. Whereas all of these certificates are handled differently in service markets, what they have in common is that they influence the buying decisions of customers. In this paper, we review state-of-the-art developments in certification with respect to service-oriented computing. We not only discuss how certificates are constructed and handled in service-oriented computing but also review the effects of certificates on the market from an economic perspective.

Managementpraktiken in KMU - Thommes, Kirsten (Controlling für kleine und mittlere Unternehmen)

Sense-Making in Social Media During Extreme Events - Stieglitz, Stefan; Bunker, Deborah; Mirbabaie, Milad; Ehnis, Christian (Journal of Contingencies and Crisis Management)

Convergence Behaviour of Bystanders: An Analysis of 2016 Munich Shooting Twitter Crisis Communication - Bunker, D.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 28th Australasian Conference on Information Systems)

Sensemaking in Social Media Crisis Communication - A Case Study on the Brussels Bombings in 2016 - Mirbabaie, Milad; Zapatka, E. (Proceedings of the Twenty-Fifth European Conference on Information Systems)

#IronyOff – Understanding the Usage of Irony on Twitter during a Corporate Crisis - Mirbabaie, Milad; Stieglitz, S.; Ruiz Eiro, M. (Proceedings of the 21st Pacific Asia Conference on Information Systems)

Mobile Unterstützung für Hilfsorganisationen in Krisensituationen - Anforderungsanalyse und prototypische Umsetzung einer Smartwatch App - Mirbabaie, Milad; Stieglitz, Stefan; Kubat, Patrick (INFORMATIK 2017)

Sensemaking and Communication Roles in Social Media Crisis Communication - Stieglitz, Stefan; Mirbabaie, Milad; Schwenner, L.; Marx, J.; Lehr, J.; Brünker, F. (Proceedings of the 13th International Conference on Wirtschaftsinformatik)

Talent management and workforce performance: The too-much-potential-talent-effect. - Krebs, Benjamin Philipp

Predicting Early Warning Signals of Financial Distress: Theory and Empirical Evidence - Sievers, Sönke; Klobucnik, Jan; Miersch, David
This study proposes a simple theoretical framework that allows for assessing financial distress up to five years in advance. We jointly model financial distress by using two of its key driving factors: declining cash-generating ability and insufficient liquidity reserves. The model is based on stochastic processes and incorporates firm-level and industry-sector developments. A large-scale empirical implementation for US-listed firms over the period of 1980-2010 shows important improvements in the discriminatory accuracy and demonstrates incremental information content beyond state-of-the-art accounting and market-based prediction models. Consequently, this study might provide important ex ante warning signals for investors, regulators and practitioners.
Keywords: Financial distress prediction; probability of default; accounting information; stochastic processes; simulation

Warum ist unser Steuersystem so komplex? Eine befragungsbasierte Analyse - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)
Die Komplexität des Steuersystems stellt auch in Deutschland ein großes Problem dar. Entgegen bisherigen Betrachtungen weist die vorliegende Befragungsstudie darauf hin, dass die Treiber für steuerliche Komplexität deutlich vielfältiger und nicht nur im Gesetz, sondern auch in den steuerlichen Rahmenbedingungen zu verorten sind. Einerseits tragen übermäßig viele Details und häufige oder umfangreiche Änderungen in erheblichem Maße dazu bei, dass Regelungen – wie solche zu Verrechnungspreisen – als komplex beurteilt werden. Andererseits erweisen sich auch inkonsistente Entscheidungen im Rahmen von Betriebsprüfungen und mangelhafte Gesetzesentwürfe als wesentliche Komplexitätstreiber. Statt einer permanenten Ausweitung von Regulierung sollte künftig der Abbau der im Beitrag identifizierten Probleme gezielt in den Fokus von Wissenschaft, Politik und Praxis rücken.
Keywords: Steuersystem; Komplexität; Steuergesetz; Steuerliche Rahmenbedingungen; BEPS

2016 Global MNC Tax Complexity Survey - Executive Summary - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren

What are the Drivers of Tax Complexity for Multinational Corporations? Evidence from 108 Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments—for example, triggered by the BEPS project—give rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this paper, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax practitioners from 108 countries. Our results show that prior complexity drivers of the tax code are still relevant, with details and changes of tax regulations being the two most influential complexity drivers. We also find evidence for new relevant complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the responses of the practitioners, we develop a concept of tax complexity that distinguishes two pillars, tax code and tax framework complexity, and illustrates the various aspects that should be considered when assessing the complexity of a country’s tax system.
Keywords: Complexity Drivers; International Comparison; Survey; Tax Complexity; Tax Practitioners

Constitutions and groups - Mauleon, Ana; Roehl, Nils; Vannetelbosch, Vincent (Games and Economic Behavior)

Signaling und Screening - Abbau von Informationsasymmetrie - Golke, Vanessa

Das Reputationssystem als bedeutendes Instrument digitaler Märkte - Moselage, Laura

Der Preis als Qualitätssignal - Hennawi, Mohammad Ziad

How Software Can Support Innovating Business Models: A Taxonomy of Functions of Business Model Development Tools - Szopinski, Daniel; Schoormann, Thorsten; John, Thomas; Knackstedt, Ralf; Kundisch, Dennis (Proceedings of the 23rd Americas Conference on Information Systems (AMCIS))
The interest in business model innovation has risen rapidly in recent years, and software tools for business model development hold great promise for supporting business model innovation. Nonetheless, virtually no design-relevant knowledge exists concerning the functions that such tools should possess. Therefore, we develop a comprehensive taxonomy that identifies characteristic functions of software-based business model development tools. For developing the taxonomy, we draw on prior research on business model innovation, process modeling, and creativity support systems, and we analyze software tools for business model development that have been proposed in practice. The resulting taxonomy can support practitioners in their tool (re-)design and investment decisions, and for researchers can serve as a preliminary step towards more advanced theories for software tools for business model development.

How Software Can Support Innovating Business Models: A Taxonomy of Functions of Business Model Development Tools - Szopinski, Daniel; Schoormann, Thorsten; John, Thomas; Knackstedt, Ralf; Kundisch, Dennis (Bosch Business Model Innovation Summit 2017)

Geschäftsmodell-Modellierungssprache/Business Model Modeling Language - Kundisch, Dennis; John, Thomas (Enzyklopädie der Wirtschaftsinformatik, GITO)

On-The-Fly Computing: Ein Referenzmodell für individualisierte IT-Dienstleistungen in dynamischen Märkten - Szopinski, Daniel; Jazayeri, Bahar; Engels, Gregor; Kundisch, Dennis (Proceedings of the Workshop Enterprise Architecture Management in Forschung und Praxis, INFORMATIK 2017, Chemnitz, Germany)
Das Enterprise Architecture Management stellt umfangreiche Methoden, Modelle und Frameworks für die Modellierung von Unternehmensarchitekturen zur Verfügung. Die Entwicklung von Software und deren Integration in IT-Landschaften ist heutzutage zunehmend von Komplexität und Unsicherheit geprägt. Dieser Beitrag (Research-in-progress) möchte ein neues Paradigma – das „On-The-Fly Computing“ – vorschlagen, um diesen Herausforderungen zu begegnen, mögliche Lösungsansätze zu diskutieren sowie erste Ergebnisse eines Referenzmodells für individualisierte IT-Dienstleistungen in dynamischen Software-Märkten dokumentieren.

Microsoft vs. the EU Commission - An analysis on product bundeling - Uden, Dennis

Algorithms for Max-Min Share Fair Allocation of Indivisible Chores - Aziz, Haris; Rauchecker, Gerhard; Schryen, Guido; Walsh, Toby (Thirty-First AAAI Conference on Artificial Intelligence (AAAI-17))
We consider Max-min Share (MmS) fair allocations of indivisible chores (items with negative utilities). We show that allocation of chores and classical allocation of goods (items with positive utilities) have some fundamental connections but also differences which prevent a straightforward application of algorithms for goods in the chores setting and viceversa. We prove that an MmS allocation does not need to exist for chores and computing an MmS allocation - if it exists - is strongly NP-hard. In view of these non-existence and complexity results, we present a polynomial-time 2-approximation algorithm for MmS fairness for chores. We then introduce a new fairness concept called optimal MmS that represents the best possible allocation in terms of MmS that is guaranteed to exist. We use connections to parallel machine scheduling to give (1) a polynomial-time approximation scheme for computing an optimal MmS allocation when the number of agents is fixed and (2) an effective and efficient heuristic with an ex-post worst-case analysis.

Solving the Container Pre-Marshalling Problem using Reinforcement Learning and Structured Output Prediction - Hetzer, Alexander; Tornede, Tanja

Editorial zur Ausgabe 33: Entwicklungsbezogene (Praxis-)Forschung - Tramm, T.; Kremer, H.-Hugo; Reinmann, G. (bwp@ Berufs- und Wirtschaftspädagogik - online)

"Quo vadis Wirtschaftspädagogik": Lehrerbildung für Berufskollegs zwischen akademischem Anspruch und Verwaltungslogiken - Kremer, H.-Hugo; Sloane, Peter F. E. (Die Fakultät für Wirtschaftswissenschaften an der Universität Paderborn: Zeitzeugen geben Einblicke in den Werdegang ihrer Fakultät)

Praxisphasen als Studienelement. Professionalisierung durch Forschendes Lernen - Kremer, H.-Hugo (Berufsschullehrerbildung in der Volksrepublik China und in der Bundesrepublik Deutschland. Professionalisierung - Kompetenzen - Herausforderungen)

Teaching under and in inequality in German Vocational Schools - Kremer, H.-Hugo (Wealth Equity Dynamics: Economics and Education Challenges)

Steuerung aus der Mitte: Relevanz und Methoden einer Rollenschärfung des mittleren Managements am Berufskolleg - Kremer, H.-Hugo; Kundisch, Heike (bwp@ Berufs- und Wirtschaftspädagogik - online)

Praxissemester in berufs- und wirtschaftspädagogischen Studiengängen - Kremer, H.-Hugo; Weyland, U. (Forschendes Lernen im Praxissemester. Zugänge, Konzepte, Erfahrungen)

Mittlere Leitungsebene an Berufskollegs. Eine kollegiale Weiterbildung zur Rollenschärfung in Auseinandersetzung mit Handlungsfeldern der Bildungsarbeit - Kundisch, Heike; Kremer, H.-Hugo

Outsourcing und Qualität im Supply Chain - Eine Gleichgewichtsanalyse - Kühn, Sarah

Crowdfunding Plattformen als Vermittler auf zweiseitigen Märkten - Eine mikroökonomische Analyse - Gunning, Justine

Entwicklungsbezogene Praxisforschung - Tramm, T.; Kremer, H.-Hugo; Reinmann, G. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Innovationsarena 3i: Handreichung zur multiprofessionellen Teamarbeit (mpT) in der Ausbildungsvorbereitung am Berufskolleg - Kückmann, Marie-Ann; Kremer, H.-Hugo

"Der Unterschied ist, die hat man erwischt" - Berufliche Bildung im Jugendstrafvollzug - Kremer, H.-Hugo; Beutner, Marc (Jugendstrafvollzug - (k)ein Ort der Bildung!?)

How do they find their place? A typology of students' enculturation during the first year at a business school - Jenert, Tobias; Brahm, Taiga; Gommers, Luci; Kühner , Patrizia (Learning, Culture and Social Interaction)
Students' experiences of their first year of studying are of prime importance for their further development in Higher Education (HE). Consequently, the first year and the related phenomena of student performance, retention, and dropout have been extensively studied. Research shows that during the first year, the individual student's ability or failure to adapt to the new socio-cultural environment influences his/her academic success. Yet, surprisingly little is known about the actual processes through which students integrate into the socio-cultural context of HE. Applying a socio-cultural approach, our qualitative interview study followed 14 university students through their first year, investigating why some students experience an easier transition into HE compared to others. Our research results in a typology of four transition types characterized by their orientation towards the socio-cultural context of studying.
Keywords: Student transition; Enculturation; Dropout; Retention

Using mixed methods to support educational design decisions in ‘bad data’contexts - Jenert, Tobias
Educational research is often conducted in practical contexts such as schools or higher education institutions and aims to contribute to the development of instructional designs or programs. Consequently, there have been repeated attempts to methodologically integrate the design aspect into educational research leading to concepts such as design-based research. Ideally, design decisions are based on clear evidence, obtained through an analysis of data gathered from the intervention. In actual projects, however, design decisions often have to be taken based on data that is incomplete, ambiguous or not meeting established scientific quality standards. We illustrate and discuss examples of an actual design research project where design decisions had to be taken in such ‘bad data’ contexts. Examples include different mixed methods configurations that helped to increase the interpretability and practical significance of the data. We will discuss methodological variants of ‘mixing’ and triangulation such as combining quantitative and qualitative data or applying different analyses on a dataset. In addition, we discuss limitations regarding the consistency between data, design decisions, and resulting effects

Investigating Networks within the field of Higher Organisation Institutions - Jenert, Tobias; Gommers , Luci
Higher education institutions (HEIs) have been described as “loosely coupled systems” (Weick, 1976) where academic disciplines have stronger cohesive forces than formal structures (Becher & Trowler, 2001). Disciplinary ties are also extremely important for the development of teaching practices in HEIs. Roxa & Martensson (2011) have shown that higher education faculty form local networks in which they share and develop teaching-related experiences. These networks are influenced by disciplinary affiliation and mediated by senior faculty (Roxa & Martensson, 2015). Considering these findings, its is not self-evident for the actors on different vertical (e.g. management, faculty and education developers) and horizontal levels (e.g. disciplines) of HEIs to work collaboratively. Therefore, the bounded nature of disciplinary networks can actually inhibit the development of educational innovations that require collaboration beyond such “disciplinary microcultures” (Kries & Nierobisch, 2016). Effective educational practices such as problem-based curricula or cross-disciplinary co-teaching require interactions that reach beyond disciplinary and hierarchical boundaries. In this study we investigate a network – “Lehren” – that was initiated in Germany to stimulate educational innovations in HEIs by overcoming the abovementioned boundaries. A series of five workshops brought together 32 potential innovators representing different disciplines, functions (management, teaching faculty, educational developers), and status groups (full professors, post-docs, others). Three of these workshop series provide a total 96 individuals who are intended to form a professional network promoting educational innovation in their respective HEIs. Providing intense support and incentives to collaborate among each other (network meetings, travel funds, online communities), the aim is to develop a heterogeneous network connecting people with, among others, different functions and from different disciplines.

Development and validation of the Reflection in Business Education Questionnaire - Jenert, Tobias; Gommers, Luci; Brahm, Taiga; Wagner , Dietrich
Student reflection is considered both a crucial feature of high-quality learning as well as an important objective in Higher Education. Despite its apparent relevance for educational practice, most of the research on reflection remains at a conceptual level (Boud & Walker, 1998; Mann, Gordon & MacLeod, 2007), whilst empirical research mainly focuses on measuring students’ reflection levels. Regarding the effectiveness of specific interventions (e.g. portfolios) to develop reflective skills, there is little empirical evidence going beyond case studies and qualitative accounts. Thus, the purpose of this research was to develop and validate an instrument for measuring student reflection in Higher Education in general and business schools in particular. The questionnaire is designed to measure students’ reflection in three dimensions: students’ reflection levels, their attitudes towards reflection, and supporting and hindering factors influencing students’ reflection processes. A pre-test was conducted at two different universities in Switzerland and Germany to validate the Reflection in Business Education Questionnaire (RIBEQ). In total, 64 students filled in the survey. Exploratory factor analyses and reliability tests showed satisfactory psychometric qualities of the RIBEQ. This study can support further research on student reflection and its development. Also, the questionnaire can be used as a diagnostic instrument for business schools to trace students’ development over time. From a practical point of view, it can also be applied to identify supporting and hindering factors at a particular higher education institution in order to develop practical interventions targeting these factors.

Educating reflective managers: Why everybody wants and nobody likes it - Wagner, Dietrich; Jenert, Tobias; Brahm, Taiga; Gommers, Luci

Die Enkulturation von Studierenden an der Hochschule – Ergebnisse einer längsschnittlichen qualitativen Untersuchung - Jenert, Tobias; Brahm, Taiga; Gommers , Luci

Warum Wirtschaftsstudierende (nicht) reflektieren. Eine empirische Untersuchung. - Jenert, Tobias; Brahm, Taiga; Wagner, Dietrich

You can’t buy my rating! On the pivotal effect of an unconditional gift on rating behavior - Gutt, Dominik; Schlangenotto, Darius; Kundisch, Dennis (Wirtschaftsinformatik Proceedings, St. Gallen, Switzerland)
The importance of online ratings on sales is widely acknowledged. Firms need to find ways of increasing the number of ratings and rating scores, but how they can achieve this effectively is less well established. In this paper we analyze the impact of an unconditional gift on customers’ rating behavior in an online field experiment. Contrary to prevalent advice, our results suggest that providing a gift is not necessarily beneficial. Younger customers are significantly less likely to rate when exposed to an unconditional gift. Regression analysis reveals that age serves as a moderator and older customers even respond slightly positive to a gift. Having detected a negative effect of gifts on rating behavior provides first indicative evidence of a possible crowding out of intrinsic motivation in the context of online ratings. This has direct implications for practitioners considering the usage of gifts to elicit online ratings.

Struktur, Prozess oder Didaktik als Ausgangspunkt? Ein integratives Modell der Curriculumentwicklung an Hochschulen - Jenert, Tobias; Barnat, M.; Salden, P.; Dilger, B. (Tagungsband DGHD Tagung 2017)

A general class of SemiGARCH models based on the Box-Cox transformation - Zhang, Xuehai; Feng, Yuanhua; Peitz, Christian

Data-driven local polynomial for the trend and its derivatives in economic time series - Feng, Yuanhua; Gries, Thomas

The Performance of Individuals, Teams, and Organizations: Empirical Evidence from the Field - Rose, Anica

When Do Managers Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren

Tax Loss Offset Restrictions and Biased Perception of Risky Investments - Mehrmann, Annika; Sureth-Sloane, Caren

Die Fakultät für Wirtschaftswissenschaften an der Universität Paderborn: Zeitzeugen geben Einblicke in den Werdegang ihrer Fakultät - Sureth-Sloane, Caren

Is there more voluntary disclosure if investors are better informed? - Ebert, Michael; Schneider, Georg Thomas

The German Precariat and the Role of Fundamental Security-Is the Unconditional Basic Income a Possible Solution for the Growing Precarity in Germany? - Gilroy, Bernard Michael; Günthner, Julia

Style Analyse im Fondsmanagement: Nicht-lineare Optimierung mit Excel Solver - Gilroy, Bernard Michael; Mykhalskyy, Vladyslav; Seiler, Volker (WiSt-Wirtschaftswissenschaftliches Studium)

Die Überprüfung der Random Walk Hypothese mit Hilfe des Variance Ratio Tests - Seiler, Volker; Kröger, Sarah; Gilroy, Bernard Michael (WiSt-Wirtschaftswissenschaftliches Studium)

Efectiveness of Official Development Assistance-Further Evidence from DAC Countries - Seiler, Volker; Taach, Evgenia